Frequency and clinical impact of different definitions of moderate aortic stenosis. (25th November 2020) - Du, Y.U; Hashimoto, G.O; Cavalcante, J; Goessl, M; Garcia, S; Ahmed, A; Lopes, B; Schmidt, C; Garberich, R; Sorajja, P
Abstract: Background: Current echocardiographic guidelines recommend five parameters to define severity of aortic stenosis (AS): peak velocity (PV), mean gradient (MG), aortic valve area (AVA), index AVA (AVAi), and dimensionless index (DI). However, the clinical utility of these parameters for patients with moderate AS largely remain unknown. Objective: To investigate the clinical profiles and outcomes of patients with moderate AS according to five different definitions for severity. Methods: Using standard echocardiographic definitions, we identified patients with moderate AS who were evaluated in our health care system from 2011 to 2012. Patient demographics, morbidities, and adverse events were reviewed, including death, heart failure (HF) admission, and aortic valve replacement (AVR). Results: We enrolled 1, 042 patients (age, 75±12 yrs; 40% women). Very few patients (4%) met all five criteria for moderate AS, while 49% had only one or two criteria met. DI was the most common parameter for defining moderate AS, employed in 93% of patients. Patients with area-based indices (i.e., AVA, AVAi, DI) had lower stroke volume index, lower mean gradients, lower peak velocities, and more morbidities in comparison to those flow-based definitions of severity (i.e., PV, MG). During a median follow-up of 5.7 years, overall survival was poor with all-cause mortality of 62.8%. Notably, there was no difference in the rates of mortality (range, 56.4 to 63.3%) or HF hospitalization (range, 28.9 to 32.2%) for groups defined by the five parameters, though patients with flow-based definitions more likely had AVR in follow-up. Conclusions: Most patients with moderate AS meet the definition for severity with one or few criteria. Regardless of the method of definition for severity, a high rate of mortality and morbidity can occur in patients with moderate AS. Further study to optimize the clinical outcomes of patients with moderate AS is warranted. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Minneapolis Heart Institute Foundation